Is the electrical conductivity of the northwestern Pacific upper mantle normal?. (11th December 2013) - Baba, Kiyoshi; Tada, Noriko; Zhang, Luolei; Liang, Pengfei; Shimizu, Hisayoshi; Utada, Hisashi
<x xml:space="preserve">Abstract</x> [1] The Normal Oceanic Mantle project, based on ocean bottom geophysical observations, has been underway since 2010 to investigate the physical state of the oceanic lithosphere and asthenosphere. We have conducted electromagnetic surveys on old (∼130 Ma) seafloor in the northwestern Pacific region, where no active tectonic processes have been identified, in order to image the electrical conductivity structure beneath the region. So far, data have been collected at four sites through a pilot survey conducted from June 2010 to August 2012. A one‐dimensional electrical conductivity model was obtained by preliminary analysis of the data by using the magnetotelluric method. The model shows that the resistive (<0.01 S m−1) lithospheric mantle is as thick as ∼80 km, and that the asthenospheric mantle below has a conductivity of ∼0.03 S m−1. The resistive layer is slightly thicker than that beneath the Philippine Sea but significantly thinner than that beneath the area off the Bonin Trench in the Pacific Ocean. There is a greater difference in age between the survey area and the Philippine Sea (0–60 Ma) than between the survey area and the area off the Bonin Trench (140–155 Ma). This comparison suggests that the relation between age and lithospheric thickness is not as simple as that predicted by the concept of lithospheric cooling. It also suggests that the lithosphere beneath the area off the Bonin Trench in the Pacific Ocean is abnormally thick if the mantle beneath the survey area in this study is "normal, " as expected from the plate cooling model.